PSYCHOSTIMULANT USE AMONG COLLEGE STUDENTS - Widanty, Batrisyia Rosieta (Journal of Psychiatry Psychology and Behavioral Research, 2024)
Introduction – Undergraduate students are transitioning to a learning curriculum, it's not unexpected that many of them are stressed out by academic and non-academic pressures. Many college students use psychostimulants, which are supplied legally or illegally, to cope with their pressures. College student consume coffee, which is known to contain caffeine, to remain awake for a longer period, improve their physical energy, and stay focused on their work. Furthermore, for academic purposes, students use psychostimulants. Although the number of college students who use psychostimulants without a prescription is modest, It's a form of drug addiction with potentially fatal effects. Methods – The author uses journals with a range of 2011-2021 to discuss the use of psychostimulants in college students. Results – Many college students consume caffeine, but studies show that they also use amphetamine non-medical prescription stimulants such as Adderall and methylphenidate, which are sold under the brand names Ritalin and Adderall. Discuss – Students commonly take non-medical prescription stimulants for a variety of reasons, including improving focus, being more productive with academic activities, working more efficiently, and reducing distractions. Sleep deprivation, sadness, abnormal movements, hallucinations, tachycardia, and loss of appetite are all common adverse effects of psychostimulants. Conclusion – Undergraduate students abuse psychostimulants because they can minimize their stresses and thus perform better in class. The usage of psychostimulants rises as the exam time approaches. Caffeine, a legal psychostimulant, has been found to improve alertness and concentration, allowing it to preserve cognitive performance that has deteriorated due to a lack of sleep.  Keywords: psychostimulant, college student, caffeine.